Penerapan Strategi Pembelajaran Card Sort dalam Meningkatkan Hasil Belajar Biologi pada Konsep Sistem Pencernaan Manusia - Wa Ode Sunarmin; Nur Alim Natsir; Muhammad Rijal (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
This study aims to determine the application of card sort learning strategies in improving biology learning outcomes on the concept of the human digestive system of grade VIII students at SMP Negeri 6 Seram Barat. The type of research used in this study is Classroom Action Research. Activities carried out in each cycle include planning, implementation, observation, and reflection. The subjects in this study were grade VIII2 students at SMP Negeri 6 Seram Barat with a total of 33 students. To obtain data on learning outcomes, it is necessary to use instruments in the form of tests and observation sheets. This research is said to be successful if, the learning outcomes achieved by students in the implementation of the test have reached the Minimum Completeness Criteria, namely individually, namely student test results have reached a value of 67 and classically student learning completeness has reached 75%. The data analysis technique used by the authors in this study is descriptive analysis.  Based on the results of the study, it can be concluded that learning using the card sort method on digestive system material in humans can improve student learning outcomes in grade VIII SMP Negeri 6 Seram Barat